2017
DOI: 10.1007/s00464-017-5607-9
|View full text |Cite
|
Sign up to set email alerts
|

The general surgeon’s perspective of rectus diastasis. A systematic review of treatment options

Abstract: BackgroundDiastasis of the rectus abdominis muscles (DRAM) is characterised by thinning and widening of the linea alba, combined with laxity of the ventral abdominal musculature. This causes the midline to “bulge” when intra-abdominal pressure is increased. Plastic surgery treatment for DRAM has been thoroughly evaluated, though general surgical treatments and the efficacy of physiotherapy remain elusive. The aim of this systematic literature review is to evaluate both general surgical and physiotherapeutic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(114 citation statements)
references
References 36 publications
2
109
0
3
Order By: Relevance
“…It is suggested that patients with DRA not causing dysfunction (DRA less than 30 mm, midline hernia or cosmetic issues) should first and foremost receive conservative management with weight control, limited hernia repair or purely aesthetic surgery. Evidence in the literature supporting physical training for symptomatic DRA is inconclusive. The main purpose of physical training is possibly to restore function, and not necessarily to reduce the diastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that patients with DRA not causing dysfunction (DRA less than 30 mm, midline hernia or cosmetic issues) should first and foremost receive conservative management with weight control, limited hernia repair or purely aesthetic surgery. Evidence in the literature supporting physical training for symptomatic DRA is inconclusive. The main purpose of physical training is possibly to restore function, and not necessarily to reduce the diastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative management with training and weight loss is generally advised as first‐line treatment. There is no strong evidence that training during pregnancy and in the postpartum period decreases the risk of persistent DRA, although some studies have reported that specific exercises could increase abdominal trunk stability and reduce some of the associated symptoms. Surgical reconstruction has been reported to restore abdominal trunk function and improve lower back pain and urinary incontinence.…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of exercise to prevent or correct diastasis recti is somewhat controversial and has been associated with mixed results. 1,17,18 Preventative exercise protocols include walking and abdominal core strengthening. Corrective exercise protocols include core strengthening, aerobic activity, and neuromuscular reeducation.…”
Section: Exercisementioning
confidence: 99%
“…Diastasis recti is a common contour abnormality affecting the anterior abdominal wall. 1 It is often associated with a negative body image, musculoskeletal pain, and occasionally urogynecological symptoms. 2 Diastasis recti manifests as a midline abdominal bulge that is the result of an attenuated linea alba.…”
mentioning
confidence: 99%
“…For these patients mesh-based repair of the midline is considered [1]. The technical variants described in the literature are diverse: open, minimally invasive and hybrid [4].…”
Section: Introductionmentioning
confidence: 99%